The Relationship of Animal Fats, Coffee, and Spicy Foods Consumption due to Incident of Gastroesophageal Reflux Disease (GERD) in Indonesia - Rafi Ashza Sejati; Hajrah Merdian Punky Saputri; Devinta Muthia Sani; Mutiara Dea Sasmita; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti (Universitas Widya Gama Mahakam Samarinda, 2024)
Abstract Background: Gastroesophageal reflux disease is a global health problem and has a varying prevalence worldwide. One of the behavioral changes in the form of unbalanced dietary factors such as consumption of spicy foods, coffee-containing beverage foods, and foods high in animal fats. Objectives: To determine the association between consumption of animal fat, coffee, and spicy food and the incidence of GERD. Research Metodes: The research design used literature review. Articles were in English and Indonesian with a time span of 2014-2024. Data obtained from the database includes Google Scholar, Pubmed, Pubmed Central, ScienceDirect, and Biomed Central. Results: This literature study obtained 10 articles that fit the inclusion and exclusion criteria. Based on the review of the articles, the consumption of animal fats, coffee, and spicy foods can increase the incidence of Gastroesophageal Reflux Disease (GERD). Conclusion: Consumption of animal fats, coffee and spicy foods are associated with the incidence of gastroesophageal reflux disease (GERD). Keywords: Gastroesophageal reflux; Coffee; Animal fats; Spicy foods Abstrak Latar Belakang: Penyakit refluks gastroesofagus menjadi permasalahan kesehatan secara global dan memiliki prevalensi yang bervariasi di seluruh dunia. Salah satu dari perubahan perilaku berupa faktor pola makan yang tidak seimbang seperti konsumsi makanan pedas, makanan minuman yang mengandung kopi, hingga makanan tinggi akan lemak hewani. Tujuan: Mengetahui hubungan antara konsumsi lemak hewani, kopi, dan makanan pedas terhadap kejadian GERD. Metode Penelitian: Desain penelitian menggunakan literature review. Artikel berbahasa Inggris dan Indonesia dengan rentang waktu 2014-2024. Data diambil melalui database Google Scholar, Pubmed, Pubmed Central, ScienceDirect, dan Biomed Central. Hasil: Studi literature ini didapatkan 10 artikel yang sesuai dengan kriteria inklusi dan eksklusi. Berdasarkan tinjauan artikel dihasilkan konsumsi lemak hewani, kopi, dan makanan pedas dapat meningkatkan kejadian Gastroesophageal Reflux Disease (GERD). Kesimpulan: Konsumsi lemak hewani, kopi, dan makanan pedas berhubungan pada kejadian Gastroesophageal Reflux Disease (GERD). Kata kunci: Gastroesophageal reflux; Kopi; Lemak hewani; Makanan pedas